Semantic mapping-based comparison of digital building LogBook and energy performance certificate models - envisaging data reuse - Sara karami; José-Paulo de Almeida; Claire Ellul; Alberto Cardoso (Developments in the Built Environment)
Building information is essential for making informed decisions about overall energy efficiency, performance, and sustainability over the lifecycle of a building. Energy Performance Certificate (EPC) and Digital Building LogBook (DBL) are the two main approaches to capture and manage building data effectively across the life cycle of buildings. While various initiatives proposed different LogBook data models, there are still drawbacks, such as heterogeneity and consensus about elements and categories (group of elements), lack of identifying the key DBL elements, lack of effectively incorporating the main elements of EPC, and providing data dictionaries. The main contribution of this ongoing research is to compare the current DBL and EPC data models through a semi-automatic and knowledge-based approach. As a result, a list of matched and unmatched elements per category was created. The comparison list provided information on the available and common elements, most representative categories and elements, and correlation between models. It also helps to include additional relevant information without causing disagreements. This paper aims to contribute to a step forward in creating a harmonized LogBook data model that may help the reuse of existing data, and hence reduction of data carbon footprint, to move forward to achieve Net-zero objectives.